Eve Teasing and Adolescents Depression (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Depression in urban female adolescents is now a growing public health problem in Bangladesh. In recent time eve-teasing (sexual harassment) has become a burning issue. Adolescent girls face both psychological and social problems due to eve-teasing and it is one of the determinants of depression of adolescent girls.Objective: The study was done to assess the level and determine the factors of depression as well as to estimate the proportion of eve teasing among female adolescent students.Materials and Methods: This cross sectional study was performed at Shahid Ramijuddin Cantonment High School, Dhaka, situated in Shahid Mannan line during a period of one year starting from January 2013 to December, 2013. The study was carried out among 203 female students of class-IX and X aged 14 to 16 years. Beck Depression Inventory (BDI) was used to measure the level of depression. Pattern of eve teasing and factors of depression was identified by a number of questions.Results: Among 203 female adolescents 122 students from class-IX and 81 students from Class-X (Mean age 15.02±0.786 years), all are unmarried, 90.6% lived in nuclear family and only 9.45% lived in joint family. This study showed 32% respondents had moderate depression, 17.7% had mild mood disturbance, 10.3 % had borderline clinical depression, 4.9% had severe or extreme depression and 35% respondents found normal. The study also revealed that 75.9% school going girls aged 14 to 16 years experienced eve teasing. Poor school performance, friction with family members, lack of friendly relationship with teachers, 03 JAFMC Bangladesh. Vol 10, No 2 (December) 2014 no communication with friends are associated with depression but the association of substance abuse, smoking habit, heavy internet use with depression was not found. This study also revealed that, 53.2% depressed adolescent girls and 46.8% adolescent girls with no depression experienced eve teasing and depression is higher among girls who experienced eve teasing. So eve teasing is an important factor for female adolescent depression.Conclusion: Among the study subjects majority of the respondents are moderately depressed and large number of students have experienced eve teasing. Eve teasing has found significant association with depression. Several factors are responsible for depression but in case of female adolescents eve teasing is one of the important factor that needs urgent attention. So, it is essential to control eve teasing for prevention of depression of adolescent girls.Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014